Syaikh Mahfudz at Tarmasi; Ulama Dunia Teladan Para Santri - Alif, Mohammad; Ansori, Muhammad Isa (Lembaga Yasin AlSys, 2024)
The homeland of the archipelago, especially the Java region, has given birth to many prestigious scholars and claimants of syar'i. This fact is revealed in historical records from the 18th to 20th centuries, where Nusantara significantly became the source of birth of international class scholars. In fact, some of them reached the level of recognition so that they were invited to become teachers in the Grand Mosque and the city of Makkah. This journal tells the story and intellectual legacy of a prominent Indonesian scholar, Shaykh Mahfudz at Tarmasi, who has become a role model for students around the world. This article discusses the life journey of Shaykh Mahfudz, the peak of his achievements in the field of religious science, and his positive influence on generations of Islamic students. Through a historical and analytical approach, this journal explains how Shaykh Mahfudz's thoughts and teachings have shaped the character and spirituality of the santri, motivating them to pursue scientific excellence and moral. By strengthening religious and ethical values, Shaykh Mahfudz at Tarmasi became an inspiring model for Islamic education.